India’s Cultural Diplomacy and Recommendations for Vietnam - Tran Bao Chau (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This study argues that Vietnam can significantly enhance its global soft power while preserving its distinctive national identity by selectively adapting key elements from India’s successful cultural diplomacy model. Through systematic analysis of India’s institutional framework, diasporic engagement strategies, and cultural assets deployment—particularly its Panchamrit doctrine and comprehensive institutional coordination—the research identifies transferable success factors that have contributed to India’s rising global influence. When applied to Vietnam’s current cultural diplomacy landscape, this analytical framework reveals both existing strengths in Vietnam’s institutional architecture, diaspora networks of approximately six million, and rich cultural heritage, alongside opportunities for more systematic coordination and strategic implementation. Based on this comparative assessment, the research proposes targeted enhancements in four priority areas: restructuring institutional architecture through a dedicated coordinating body within Ministry of Foreign Affairs, developing structured diasporic engagement beyond remittances, deploying cultural assets through a three-dimensional approach (historical legacy, contemporary dynamism, and future orientation), and expanding digital diplomacy capabilities. The findings demonstrate that while Vietnam possesses significant cultural resources and institutional foundations, a more comprehensive approach would substantially amplify its cultural diplomacy effectiveness on the global stage. Received 15th December 2024; Revised 15th April 2025; Accepted 30th April 2025